2007
DOI: 10.1140/epjb/e2007-00322-1
|View full text |Cite
|
Sign up to set email alerts
|

Correlation and volatility in an Indian stock market: A random matrix approach

Abstract: We examine volatility of an Indian stock market in terms of aspects like participation, synchronization of stocks and quantification of volatility using the random matrix approach. Volatility pattern of the market is found using the BSE index for the three-year period 2000-2002. Random matrix analysis is carried out using daily returns of 70 stocks for several time windows of 85 days in 2001 to (i) do a brief comparative analysis with statistics of eigenvalues and eigenvectors of the matrix C of correlations b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…For UT, it is a extremely-high-volatility segment that coincides with the high-volatility segment in other sectors. the nontrivial cross-correlations between different financial time series using random matrix theory [122][123][124][125][126][127][128][129]. In all these studies, the cross-correlations were computed either over the entire data period, or over sliding windows.…”
Section: Tablementioning
confidence: 99%
“…For UT, it is a extremely-high-volatility segment that coincides with the high-volatility segment in other sectors. the nontrivial cross-correlations between different financial time series using random matrix theory [122][123][124][125][126][127][128][129]. In all these studies, the cross-correlations were computed either over the entire data period, or over sliding windows.…”
Section: Tablementioning
confidence: 99%
“…Various volatility estimates and diagnostic tests indicated volatility clustering, i.e., shocks to the volatility process persist and the response to news arrival was asymmetrical, meaning that the impact of good and bad news is not the same. Kulkarni and Deo (2005) observed the volatility of an Indian stock market in terms of aspects like participation, synchronization of stocks and quantification of volatility using the random matrix approach. Pandey (2005) compared the empirical performance of various unconditional volatility estimators and conditional volatility models (GARCH and EGARCH) using time-series data of S&PCNX Nifty, a value-weighted index of 50 stocks traded on the National Stock Exchange (NSE), Mumbai Estimates computed by various estimators and conditional volatility models over non overlapping one-day, five-day and one-month periods are compared with the "Realized Volatility" measured over the same period.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Tulino described the application of the basic constraints of wireless communication channels on the basis of stochastic matrix theory [4]. Varsha Kulkarni analyzed the volatility of the Indian stock market based on stochastic matrix theory [5]. Based on the knowledge of stochastic matrix, Meng and Xie used absorption rate, linear regression and clustering methods to study the correlation degree and division of the American real estate market, and found that the risk of the American estate market was very high and the whole market was unstable [6,7].…”
Section: Literature Review Of Stochastic Matricesmentioning
confidence: 99%